PERAN BRAND IMAGE DALAM MEMEDIASI PENGARUH CELEBRITY ENDORSER TERHADAP PURCHASE INTENTION (STUDI PADA KONSUMEN KOPI JANJI JIWA DI KOTA DENPASAR) - Devanagiri, Dewa Gede Agung Wikrama Aditya; Rastini, Ni Made (E-Jurnal Manajemen; Vol 11 No 11 (2022), 2022)
Promise Jiwa is one of the coffee shops in Indonesia that uses celebrity endorsers in marketing their products. This study aims to analyze the effect of brand image in mediating the influence of celebrity endorsers on purchase intention at Kopi Janji Jiwa in Denpasar City. The location of this research is the Jiwa Jiwa in Denpasar City. The population of this study includes consumers who live in Denpasar City with a total sample of 130 samples. The sample was determined by purposive sampling. Collecting data using survey methods and research instruments in the form of a questionnaire measured by a 5-point Likert scale. Data analysis was performed using Path Analysis through SPSS. The results of this study indicate that celebrity endorser has a positive and significant effect on purchase intention and brand image, brand image has a positive and significant effect on purchase intention, and brand image is able to mediate the influence of celebrity endorser on purchase intention. The theoretical implications of this study support the results of previous studies related to purchase intention. The practical implications of this research are as material for consideration and input for the management of Janji Jiwa in Denpasar City in marketing their products. For further researchers, they can add variables that can affect purchase intention, expand the scope of research, or change the research location. Keywords: celebrity endorser; brand image; purchase intentions; Soul Promise Coffee